THE EFFECTIVENESS OF THE SOCIAL SERVICE OFFICE IN THE NON-HARVEST FOOD AID DISTRIBUTION PROGRAM IN DATU KUNING VILLAGE, AMUNTAI TENGAH DISTRICT - Reka Amalia; Sugianor Sugianor; Mawarti Mawarti (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
Poverty is a major social problem that requires targeted handling through social assistance such as the Non-Cash Food Assistance Program (BPNT). This study aims to analyze the effectiveness of the Social Service's performance in implementing the BPNT program in Datu Kuning Village, Amuntai Tengah District. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the effectiveness of the Social Service's performance has not been optimal. Although the aspects of planning and aid benefits have been effective, the indicators of targeting accuracy, educative socialization, and program monitoring are still considered less effective. The main supporting factor is the availability of strategic e-warungs, while the inhibiting factors include inconsistent distribution schedules, low public understanding, and weak direct supervision in the field. In conclusion, strengthening the monitoring function and participatory data validation is urgently needed to improve the quality of social assistance services.